1978
DOI: 10.1177/070674377802300304
|View full text |Cite
|
Sign up to set email alerts
|

Lunacy the Relation of Lunar Phases to Mental III-Health

Abstract: On passe en revue la littérature concernant la croyance qu'un comportement anormal puisse être causé par les phases de la lune ou soit en relation avec celle-ci. On conclut qu'il n'y a eu aucune démonstration satisfaisante, c'est-à-dire sans équivoque et répétée, d'une corrélation entre les phases de la lune et une conduite anormale, mais que ce concept n'est peut-être pas défini d'une manière assez adéquate pour permettre une telle démonstration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
3
0

Year Published

1979
1979
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…Seven years have elapsed since Campbell and Beets (1978) concluded that “lunar phase is not related to human behavior” (p. 1123). Their conclusion is similar to those reached by astronomers (Abell & Singer, 1981), physicists (Culver & Ianna, 1979), and other psychologists (Coles & Cooke, 1978; Cooke & Coles, 1978). Further, books championing the lunar hypothesis have received skeptical and, in a few cases, hostile reviews (Abell, 1979; Earley, 1978; Ornstein, 1978; Rotton, 1982a).…”
supporting
confidence: 83%
See 1 more Smart Citation
“…Seven years have elapsed since Campbell and Beets (1978) concluded that “lunar phase is not related to human behavior” (p. 1123). Their conclusion is similar to those reached by astronomers (Abell & Singer, 1981), physicists (Culver & Ianna, 1979), and other psychologists (Coles & Cooke, 1978; Cooke & Coles, 1978). Further, books championing the lunar hypothesis have received skeptical and, in a few cases, hostile reviews (Abell, 1979; Earley, 1978; Ornstein, 1978; Rotton, 1982a).…”
supporting
confidence: 83%
“…Because Garzino (1982b) claimed that previous reviewers had been selective in their choice of references, we took several steps to locate relevant articles and unpublished papers. One was to retrieve references from previously cited reviews of the literature (e.g., Coles & Cooke, 1978) and books linking lunar cycles and behavior (e.g., Katzeff, 1981). Another was to obtain a computer listing of articles published after 1978, when Campbell and Beets completed their review, from three abstract services (Psyc INFO , ERIC , and SOCIAL SCISEARCH ).…”
Section: Methodsmentioning
confidence: 99%
“…In fact, "if an hypothesis does not hold up under replication attempts that are methodologically similar to the original srudies, then doubt should be cast upon the truth of the hypothesized relationship" ( Campbell, 1982, p. 420). Coles and Cooke ( 1978) have expressed a similar conviction: "The test for the falsification of scientific fact is replication of a particular study by an independent investigator" (p. 150). However, several reviewers (Campbell, 1982;Rotton & Kelly, 1985) have not appreciated the scientific meaning of replication.…”
mentioning
confidence: 91%
“…I n the past 25 years phenomena suspected of being influenced by the full moon have included misbehaviors among mentally retarded persons and the mentally ill, plus crisis and poison center calls, accidental injuries, suicide, emergency room visits, drug overdose, and human birth and menstrual cycles, among others. As one reads the literature one becomes aware of the controversy as some researchers cite evidence for the hypothesis (Coles & Cook, 1978;Stone, 1976;Leiber & Sherin, 1972;Leiber, 1978;Menaker, 1967;Templer, Veleber, & Brooner, 1982;Odera & Klein-Schwartz, 1983), while other researchers cite evidence against it (Abell & Greenspan, 1979;Culver, Rotton, & Kelly, 1988;Kelly & Rotton, 1983;Lester, 1979;Michelson, Wilson, & Michelson, 1979;Sanduleak, 1985;Pokorny & Jachimyczky, 1974). As Kelly, Rotton, and Culver (1985-86) 'Address correspondence to William E. Hicks-Caskey, Ph.D., P O Box 18940A, East Tennessee State University, Johnson City, T N 37614-0002. wrote in their review of the literature, "For every study that had found that people behave more strangely than usual when the moon is full, another had found that people's behavior was not affected" (p. 131).…”
mentioning
confidence: 99%